The Adaptation Differences in Terms of Gender on Students in Ulumul Qur'an Stabat Islamic Boarding School - Wahyuni, Nini Sri; Barus, Nurhayati (Budapest International Research and Critics University, 2020)
This research aims to adjustment see the difference self in terms of gender performed by students of boarding schools, where good adaptability are in case there is no excess, no emotional obtained psychological mechanism, a feeling of frustrated personal, ability to learn, the utilization of the experience of the past, realistic and objective stance and rational considerations and direct self. Where the subject of the research is male and female students Class VII MTs ulumul qur'an Stabat that add up to 60 students using simple random sampling technique. Measuring instrument used is liket scale consisting of 64 item and after do try out at 40 students, a valid item becomes 55 item. Based on the data analysis noted that: there is a significant difference in adaptability on student boarding schools in terms of gender, the results of data analysis with the correlation of the T-Test revealed differences with the coefficient of T-Test, F = 1,377 with P = 0000 < 0050. It is declared that the adaptability of male students is higher than female students. Females students having adaptability which are with the empirical mean 145.17 and hypothetic 137.5. Based on the analysis of the data, then the hypothesis presented in this research were declared admissible, namely distinction adaptability according to the gender in which conformity to higher male than female.